Potential impact of coronaviruses upon cardiovascular system under COVID-19 pandemic - L.O. Tkachenko; O.A. Yepanchintseva; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
The pandemic of the new coronavirus infection COVID-19 covered more than 180countries of the world. Acute respiratory syndrome caused by coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has reached a pandemic level and has affected more than 180 countries. A significant proportion of patients have cardiovascular disease and / or cardiac risk factors. The pathogenesis of the virus on the body, clinical manifestations of the disease, features of the course of infection in patients with cardiovascular disease are discussed. The issues of routing, surgical and therapeutic treatment of patients with cardiovascular diseases, especially emergencies (acute myocardial infarction, decompensation of heart failure on the background of valvular heart disease) have become difficult. There are no clear algorithms and recommendations for the treatment of such patients in a pandemic and differ in different countries. There are many unresolved issues regarding the side effects of drugs used to treat coronavirus infection on the cardiovascular system, as well as their interactions with conventional drugs in such patients, especially drugs that affect the renin-angiotensin aldosterone system. The review reflects the main trends of the general approach in understanding organizational and therapeutic procedures in the care of patients with cardiovascular disease during the pandemic COVID-19.